PENGARUH PRESTASI, LOCUS OF CONTROL, RESIKO, TOLERANSI AMBIGUITAS, PERCAYA DIRI, DAN INOVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Jusmawi Bustan (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This study focused on the psychological factors that determine the background for students to become entrepreneur. The purpose of the study to determine the effect of need for achievement, locus of control, risk, tolerance of ambiguity, self-confidence, innovation seeks to interest students. This study used a survey method approach to determine the influence between variables. The sample was students who have exhausted all departments entrepreneurship courses by 93 respondents. The sampling technique used was purposive random sampling. The instrument in this study was a questionnaire using multiple regression analysis using SPSS 19 for Windows. The results showed that there was a significant effect simultaneous between achievement, locus of control, risk, tolerance, confidence and innovation with interest in entrepreneurship. Then, partial no significant influence achievement with interest in entrepreneurship. No there is no significant effect of locus of control with interest in entrepreneurship. There is a significant effect of risk with interest in entrepreneurship. No significant effect of tolerance with interest in entrepreneurship. There is a significant effect of self-confidence with interest in entrepreneurship. There is asignificant effect of innovation with interest in entrepreneurship. The parties involved in developing entrepreneurship should be of increasing concern to the students so that the spirit of entrepreneurship better.